Building a Local Design and Entrepreneurship Ecosystem. (2015) - Collins, Paul K.
Abstract: Design: and creativity are becoming greatly sought out skills in leading industries around the world, big businesses are developing the "Chief Design Officer" to engage with strategic and company shaping discussions. Design as an economic driver is now abundantly clear with companies such as Nike and Apple leading this way of thinking, but how do we as Australian industry capture this and how do we instil "creativity" into our secondary school and university level education to drive the next level of innovation and development. The local region where Deakin University is situated has undergone significant changes in the last 10 years, what was once an economy dominated by oil, automotive and metal production industries has been wound down to a local economy dominated by health, services and education. However, manufacturing and design being the front end of manufacturing is still a key economic driver this study is looking at the embryonic initiatives undertaken to build an ecosystem of design and entrepreneurship in a regional area. Several aspects will be looked at, high school and university student engagement in the process, established SME's and start-up culture. With the establishment of an ecosystem it is believed that success will breed success. With student engagement showing that being creative and playing can yield tangible results, it also gets students comfortable with the element of risk. The efforts of Deakin University is about providing the framework and scaffolding for students to pursue a start-up idea and test it validity. The final part of the ecosystem is for SME's and recent start-ups to share their success stories and acting as mentors as future start-ups emerge. By creating an ecosystem that is driven by design, manufacturing and entrepreneurship key economic outcomes will be generated; a regional area will be more resilient to economic uncertainty and ultimately a cohort of innovative thinkers that will generate value for their community.